(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
This article examines the concept, structure, and didactic features of students’ independent learning in modern educational systems. Independent learning is considered a key factor in developing students’ critical thinking, self-regulation, and lifelong learning skills. The paper analyzes the main components of independent learning, including motivation, cognitive activity, and self-assessment. Furthermore, special attention is given to the didactic conditions and methods that enhance the effectiveness of independent study. The study highlights the importance of integrating innovative teaching technologies and learner-centered approaches to foster autonomy and responsibility among students.